PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT CAHAYA BUANA INTITAMA (CBI) SENTUL, KABUPATEN BOGOR - Aditya Dimas Artandi; Fathan Arif (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the effect of communication and the work environment on employee performance at PT Cahaya Buana Intitama Sentul, Bogor Regency. This research uses a quantitative approach with a sample of 66 employees, a sampling technique using saturated sampling. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and F test. The results of the research show that communication (X1) and the work environment (X2) have a significant effect on employee performance with the regression equation Y = 4.578 + 0.338X1 + 0.547X2. The correlation coefficient value obtained was 0.867, meaning it has a very strong relationship. The value of the coefficient of determination or contribution of influence simultaneously is 0.867 or 86.7% while the remaining 13.3% is influenced by other factors. The test results show that the calculated F value > F table or (95.138 > 3.140), this is also reinforced by the significance < 0.050 or (0.000 < 0.050). Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence of communication and the work environment on employee performance.